Propaganda and promotional activities : an annotated bibliography : prepared under the direction of the Advisory Committee on Pressure Groups and Propaganda, Social Science Research Council - Lasswell, Harold D. [Dwight], 1902-1978 (Minneapolis ; Minnesota)
xvii, 450 s.